1976
DOI: 10.1126/science.193.4254.687
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoid Differentiation in Fern Spores: Experimental Manipulation

Abstract: Germination in spores of the fern Onoclea sensibilis is initiated by an asymmetric division that partitions the spore into two cells of unequal size. The unequal daughter cells differentiate immediately into distinct types. When spores are germinated on the surface of solutions of methanol, the initial division is symmetrical, and the daughter cells from this equal division develop into the same type of cell. The differentiation of a rhizoid from the smaller cell in untreated spores is suppressed by methanol t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1980
1980
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…If this movement was prevented, no differentiation of a rhizoid occurred during the subsequent mitosis (Miller and Greany, 1976). By contrast, the present study clearly showed that the nucleus remained in the corner of the tetrahedronshaped dormant spore of A. capillus-veneris (Fig.…”
Section: Discussion Premitotic Positioning Of the Nucleus In Fercontrasting
confidence: 45%
“…If this movement was prevented, no differentiation of a rhizoid occurred during the subsequent mitosis (Miller and Greany, 1976). By contrast, the present study clearly showed that the nucleus remained in the corner of the tetrahedronshaped dormant spore of A. capillus-veneris (Fig.…”
Section: Discussion Premitotic Positioning Of the Nucleus In Fercontrasting
confidence: 45%
“…The switch from division to differentiation in spermatids may be analogous to the switch to differentiation after asymmetric cell division in plants (Bunning, 1952;Miller and Greany, 1976). The nucleus in the new small cell with a very low ratio ofcytoplasm to nuclear volume begins to differentiate immediately.…”
Section: Discussion-division Phase -mentioning
confidence: 98%